Bulgaria's EU Funds Absorption : Maximizing the Potential! - Paliova, Iana (IMF Working Papers; Working Paper, 2014)
This paper focuses on EU structural and cohesion funds assistance to Bulgaria during the 2007-13 program period. Initial weaknesses resulted in a low absorption rate, which was mitigated by increasing advance payments; applying electronic application and reporting procedures; simplifying and unifying tender processes; and strengthening the role of international financial institutions and banks in project preparation, evaluation and monitoring. The possible impact on growth and potential output is briefly discussed, while the risks of improper absorption are acknowledged. Valuable lessons have been learned, but it is recommended that additional steps be taken for the next program period 2014-20.